Orbital Desmoid-Type Fibromatosis: A Case Report and Literature Review. (8th March 2018) - Moro, Alessandro; De Angelis, Paolo; Gasparini, Giulio; Pelo, Sandro; Petrone, Gianluigi; Lucci Cordisco, Emanuela; Garagiola, Umberto; D'Amato, Giuseppe; Saponaro, Gianmarco
Abstract : Purpose . Desmoid-type fibromatosis is a benign fibrous neoplasia originating from connective tissue, fascial planes, and musculoaponeurotic structures of the muscles. Currently, there is no evidence-based treatment approach available for desmoid fibromatosis. In this article, a case of a patient in the pediatric age affected by desmoid fibromatosis localized in the orbit is presented. The aim of the article is to describe this unusual and rare location for the desmoid fibromatosis and outline the principle phases in the decision-making process and the therapeutic alternatives for a patient affected by desmoid fibromatosis. Methods . The protocol of this review included study objectives, search strategy, and selection criteria. The primary end point of this study was to analyze the head and neck desmoid fibromatosis. The secondary end point was to identify the available therapies and assess their specific indications. Results . The mean age of patients was 18.9 years ranging from 0 to 66, and 52% were female. A bimodal age distribution was observed, and two age peaks were identified: 0–14 years (57%) and 28–42 years (18%). The most common involved areas were the mandible (25%) followed by the neck (21%). In 86% of the cases, the treatment was the surgical resection of the disease, and only in 5% of the cases, the surgical resection was followed by adjuvant radiotherapy. Conclusion . The orbital location is extremely rare, especially in the pediatric population. The management of desmoid fibromatosis is based on the function preservation and the maintenance of a good quality of life, but in case of symptomatic patients or aggressive course of the disease or risk of functional damages, the surgical approach may be considered. Therapeutic alternatives to surgical resection are radiotherapy and systemic therapy.